Digital Agriculture Profile: Grenada - Kropff, Wietske; Eitzinger, Anton; Hasiner, Eva; Schroeder, Kateryna; Treguer, David; Juergenliemk, Armine; Horst, Alexandra; Jarvis, Andy (Food and Agriculture Organization of the United Nations, 2021)
This Digital Agriculture Profile for Grenada leverages the expertise of stakeholders to evaluate the current landscape of digital agriculture in the country, including its key players across value chains, the main barriers faced, and the potential to overcome these barriers through the adoption of innovative technologies.